Peningkatan Kapasitas Produksi dan Efisiensi Manajemen pada Usaha Rendang Kemasan di Pasaman Barat melalui Modernisasi Peralatan dan Digitalisasi Pencatatan Produksi - Setiawan, Rizki Dwi; Juliyarsi, Indri; Melia, Sri; Aulia H, Surya; sandy, Ikhlas Pratama; Azzahra, Chairilisa (LPPM Universitas Andalas, 2025)
Micro, small, and medium-sized food enterprises in Indonesia face persistent challenges related to productivity and digitalization, as many still rely on manual processing and non-digital record-keeping, resulting in low efficiency and competitiveness. This condition is also evident in the Rendang Bu Pit MSME in Pasaman Barat, which operates with traditional equipment and basic bookkeeping. This community engagement program aimed to enhance production capacity and managerial efficiency through equipment modernization and digital digitization. A participatory action approach was employed, consisting of problem identification, technology transfer, production management training, implementation of semi-automated equipment, development of a spreadsheet-based digital dashboard, and continuous mentoring. Evaluation was performed using a before–after comparison of production performance. The results showed substantial efficiency improvements: coconut milk extraction decreased from ±60 minutes to ±15 minutes (75% efficiency gain); beef rendang cooking time decreased from ±6 hours to ±3.5 hours (40%); and clam rendang from ±4 hours to ±2.5 hours (37%). The use of a vacuum sealer increased packaging efficiency by up to 50% while extending product shelf life. The digital dashboard enabled integrated and real-time recording of raw materials, production output, sales, and profit/loss, thereby supporting data-driven decision-making. This program demonstrates novelty through the integration of semi-automated processing technology with an end-to-end digital system at the MSME scale, and its significance lies in strengthening digital transformation among food-sector MSMEs. The model is highly replicable for similar businesses to improve productivity, quality consistency, and competitiveness of the rendang industry at local and regional levels.